2009
DOI: 10.1176/appi.ps.60.8.1075
|View full text |Cite
|
Sign up to set email alerts
|

National Variation of ADHD Diagnostic Prevalence and Medication Use: Health Care Providers and Education Policies

Abstract: To better understand the association between a state's health care provider characteristics and both diagnostic prevalence and medication use, it may be fruitful to examine the content of provider continuing education programs, including the recommendations of major health professional organization guidelines to treat ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…However, these data do allow for ecological analyses of changes in policies and demographic characteristics, as conducted by Fulton and colleagues. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these data do allow for ecological analyses of changes in policies and demographic characteristics, as conducted by Fulton and colleagues. 33 …”
Section: Discussionmentioning
confidence: 99%
“…A number of contextual factors are known to influence the frequency with which childhood ADHD is diagnosed, including increased awareness efforts, educational policies, physician characteristics, cultural factors, and changes in public perception. 3336 Other factors, such as increased confidence to treat ADHD among clinicians and increased exposure to etiologic factors (e.g., environmental contaminants) may also play a role. The magnitude of increases documented with these cross-sectional data warrant future efforts to more fully understand the factors impacting ADHD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey in 2003 by the Centers for Disease Control and Prevention (CDC) estimated that statewide rates of ADHD among children ranged from 5.0% to 11.1% and that treatment rates varied between 2.2% and 6.5% (9). Wide variation in pediatric treatment rates has been reported within single states (10-12), among states (9,13,14), among different regions of the United States (15,16), and among counties (17,18). The only study (14) of adult treatment rates, derived from a sample of insurance claims, estimated that .8% of adults used ADHD medications, but the extent and nature of geographic variation in adult treatment have not been examined.…”
mentioning
confidence: 99%
“…Studies of geographic variation in use of prescribed stimulants have found correlations with a number of contextual characteristics, including supply of physicians, average age of physicians, school characteristics, and characteristics of the county’s population, such as age and gender distributions, per capita income and employment rates, education levels, household structure, racial-ethnic composition, insurance coverage, lead exposure levels, and even proximity of child’s residence to airports or parks (11,15,17,18). Two studies of county-level variation nationwide exist but only measure amounts of stimulants distributed per county resident (18) or amounts per estimated numbers of ADHD-diagnosed children (17) and not prevalence of treated patients.…”
mentioning
confidence: 99%
“…There is also substantial state-based variability in rates of medicated ADHD, from 2% in Nevada to 10% in Kentucky and Louisiana (Susanna N. Visser et al, 2014). State variation in prevalence has been partially explained by state demographics (race and public insurance coverage) and the characteristics of the state’s physicians; higher state proportions of younger physicians (<45 years) are associated with higher state-based rates of diagnosed and medicated ADHD (Fulton et al, 2009). Ecological analyses suggest that school policies, practices, and accountability laws may contribute to state-based variation in ADHD rates.…”
Section: Introductionmentioning
confidence: 99%